Commentary : mesenchymal stem cells : a new piece in the puzzle of COVID-19 treatment - Carvalho, Juliana Lott de (2021)
A Commentary on Mesenchymal Stem Cells: A New Piece in the Puzzle of COVID-19 Treatment By Saldanha-Araujo F, Melgaço Garcez E, Silva-Carvalho AE and Carvalho JL (2020). Front. Immunol. 11:1563. doi: 10.3389/fimmu.2020.01563.